Texts with Various Levels of Hardness, Reading Comprehension and Reading Motivation: I+1 Versus I-1 - Namaziandost, Ehsan; Rahimi Esfahani, Fariba; Nasri, Mehdi (ELT Forum: Journal of English Language Teaching, 2019)
Considering the vital role of comprehensible input, this study attempted to compare the effects of input with various difficulty levels on Iranian EFL learnersâ€™ reading comprehension and reading motivation. To fulfil this objective, 54 Iranian pre-intermediate EFL learners were selected from two intact classes (n = 27 each). The selected participants were randomly assigned to two equal groups, namely â€œi+1â€ (n=27) and â€œi-1â€ group (n=27). Then, the groups were pretested by a researcher-made reading comprehension test. After carrying out the pre-test, the treatment (i.e., extensive reading at different levels of difficulty) was practiced on the both groups. The participants in â€œi+1â€ group received reading passages beyond the current level, on the other hand, the â€œi-1â€ group received those reading passages which were below their current level. After the instruction ended, a modified version of pre-test was conducted as posttest to determine the impacts of the treatment on the studentsâ€™ reading comprehension. The obtained results indicated that there was a significant difference between the post-tests of â€œi+1â€ and â€œi-1â€ groups. The findings showed that the â€œi+1â€ group significantly outperformed the â€œi-1â€ group (p < .05) on the post-test. Moreover, the findings indicated that â€œi+1â€ groupâ€™s motivation increased after the treatment. The implications of the study suggest that interactive type of input is beneficial to develop studentsâ€™ language skills. Keywords: Comprehensible Input; Extensive reading; Foreign language reading motivation; Input; Reading comprehension; Text difficulty level